2014
DOI: 10.1039/c4tc00659c
|View full text |Cite
|
Sign up to set email alerts
|

Activatable triplet photosensitizers: magic bullets for targeted photodynamic therapy

Abstract: The review summarizes methods to design tumor cells/tissue targeted photodynamic therapeutic compounds to produce cytotoxic singlet oxygen upon photoirradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
111
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 142 publications
0
111
0
Order By: Relevance
“…In this construct, watersoluble pillar [5]arene was used as a host (carrier) for a diiodo-BODIPY derivative that contains a quaternary ammonium tail. [25] Supramolecular vesicles (pseudorotaxane) formed with pillar [5]arene and the modified dye are highly stable under physiological conditions but undergo disassembly in an acidic environment to release the dye. In a proof of principle study, the vesicles were found to be cytotoxic only to A549 cancer cells under 690 nm irradiation, suggesting that they disassemble Adv.…”
Section: Low Ph Of Tumor Microenvironments Activates Cancerspecific Imentioning
confidence: 99%
See 3 more Smart Citations
“…In this construct, watersoluble pillar [5]arene was used as a host (carrier) for a diiodo-BODIPY derivative that contains a quaternary ammonium tail. [25] Supramolecular vesicles (pseudorotaxane) formed with pillar [5]arene and the modified dye are highly stable under physiological conditions but undergo disassembly in an acidic environment to release the dye. In a proof of principle study, the vesicles were found to be cytotoxic only to A549 cancer cells under 690 nm irradiation, suggesting that they disassemble Adv.…”
Section: Low Ph Of Tumor Microenvironments Activates Cancerspecific Imentioning
confidence: 99%
“…However, aPSs are activated at the site where therapy is desired by tumor-associated stimuli. [4,5] Since aPSs can have their PDT and tumor imaging capabilities at the same time, they rejuvenate the field of PDT by making it highly possible to reduce the side effects and unselective killing of healthy cells. Below, we present a current summary of the progress that has been made in the development of aPSs as phototheranostic agents to assess tumor microenvironments.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, 36 Tang et al, (2012) isolated some cyclic tetrapyrrolic photosensitizers from C. patentiramea and demonstrated that they exhibit important photo toxicity against HL60 promyelocytic leukemia cells. To date, a number of photosensitizers derived from natural products have been clinically approved for the photo dynamic therapy of specific cancers (37). Furthermore, 38 Laungsuwon and Chulalaksananukul (1995) found that the ethyl acetate extract of C.glomerata possesses growth inhibitory activity (IC50=1420 μg/g) against the KB cell lines (epidermoid carcinoma of the oral cavity) in vitro.…”
Section: Discussionmentioning
confidence: 99%